Linguistic Eschatology: Babel and Pentecost in Seventeenth-Century Linguistic Thought. (1st May 2013) - Cram, David
<x xml:space="preserve">Abstract</x> The aim of this paper is to position the seventeenth-century quest for a philosophical language within an eschatological framework of first and last things. Modern accounts of these projects often focus exclusively on theological first things: namely the Adamic language and its fragmentation at the destruction of the Tower of Babel. But Babel had its equally important anti-type in the biblical account of speaking in tongues at Pentecost. The primary focus of the paper will be to explore seventeenth-century interpretations of Pentecost, which, rather unexpectedly from a modern point of view, turn out to involve not glossolalia, in the narrow sense of speaking in the tongues of angels rather than the tongues of men, but xenololia, in the equally narrow sense of speaking in a human language that one has never learned.